Students' Intuitiveness in Solving Mathematical Analogy Problems - Yahdillah, Nawal; Nusantara, Toto; Hidayah, Indriati Nurul (PRISMA, 2025)
This study aims to describe students' intuition in solving mathematical analogy problems, which is an essential aspect of analogical reasoning in 21st-century education. The research employed a descriptive qualitative approach. The population in this study was high school students from East Java, with the research subjects comprising students from SMAN 1 Ngoro Mojokerto and SMA Katolik St. Albertus Malang. A total of 31 students participated as samples. Data were collected using an analogy problem related to the system of equations with three variables and a validated interview guideline. The data were analyzed qualitatively by categorizing student responses and identifying intuition characteristics. The results showed that 16 out of 31 students used intuition in solving analogy problems. Their intuition was classified into two main categories: (1) catalytic inference and common sense, shown by 3 students who gave quick and concise answers using prior knowledge, and (2) the power of synthesis and common sense, found in 13 students who gave more elaborate answers based on their understanding and experience. The findings highlight the significant role of intuition in mathematical learning and suggest the need for instructional strategies that support intuitive reasoning.